2009
DOI: 10.1105/tpc.109.067041
|View full text |Cite
|
Sign up to set email alerts
|

Members of theLBDFamily of Transcription Factors Repress Anthocyanin Synthesis and Affect Additional Nitrogen Responses inArabidopsis   

Abstract: Nitrogen (N) and nitrate (NO 32 ) per se regulate many aspects of plant metabolism, growth, and development. N/NO 3 2 also suppresses parts of secondary metabolism, including anthocyanin synthesis. Molecular components for this repression are unknown. We report that three N/NO 3 2 -induced members of the LATERAL ORGAN BOUNDARY DOMAIN (LBD) gene family of transcription factors (LBD37, LBD38, and LBD39) act as negative regulators of anthocyanin biosynthesis in Arabidopsis thaliana. Overexpression of each of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
471
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(489 citation statements)
references
References 109 publications
10
471
1
7
Order By: Relevance
“…The C motif containing four cysteines is conserved in all LBD proteins and is predicted to form a DNA-binding zinc finger, while the lessconserved Leu-zipper-like motif is predicted to form a coiled-coil motif involved in homodimerization or other protein-protein interactions (Shuai et al, 2002;Majer and Hochholdinger, 2011). Nuclear localization and DNA-binding activity shown for some members suggests LBD proteins function as transcription factors (Shuai et al, 2002;Husbands et al, 2007;Naito et al, 2007;Rubin et al, 2009). Indeed, the LOB domain is sufficient for DNA-binding activity, and Husbands et al (2007) found several LBD members could bind a 6-bp consensus motif (G)CGGC(G), termed the LBD motif, with a broader sequence of A/T C/T GCGGCG C/T/G A/G A/T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C motif containing four cysteines is conserved in all LBD proteins and is predicted to form a DNA-binding zinc finger, while the lessconserved Leu-zipper-like motif is predicted to form a coiled-coil motif involved in homodimerization or other protein-protein interactions (Shuai et al, 2002;Majer and Hochholdinger, 2011). Nuclear localization and DNA-binding activity shown for some members suggests LBD proteins function as transcription factors (Shuai et al, 2002;Husbands et al, 2007;Naito et al, 2007;Rubin et al, 2009). Indeed, the LOB domain is sufficient for DNA-binding activity, and Husbands et al (2007) found several LBD members could bind a 6-bp consensus motif (G)CGGC(G), termed the LBD motif, with a broader sequence of A/T C/T GCGGCG C/T/G A/G A/T.…”
Section: Discussionmentioning
confidence: 99%
“…The LBD family has previously mainly been studied in regard to plant development with roles in defining the boundaries between organs (Shuai et al, 2002;Majer and Hochholdinger, 2011;Feng et al, 2012). Other LBDs have been shown to have functions in the regulation of nitrogen metabolism and anthocyanin biosynthesis (Rubin et al, 2009). Functions of LBD20 were previously unknown, and our results demonstrate LBD20 is the first member of the LBD family shown to have a role in JA signaling and plant-pathogen interactions.…”
mentioning
confidence: 99%
“…As NIN, which is necessary for symbiosis between legumes and nitrogen fixing bacteria, had been proposed as a putative transcription factor 20 , NLP7 is also speculated to be a regulatory protein associated with nitrogen assimilation. The LBD genes are also proposed to encode transcription factors associated with nitrate-responsive gene expression, because overexpression of LBD37, LBD38 or LBD39 represses the expressions of nitrate transporter and NR genes in Arabidopsis 21 . Another Arabidopsis gene, GNC, has also been identified as a nitrateinducible gene encoding a putative transcription factor of the GATA family 22 .…”
mentioning
confidence: 99%
“…Within minutes, primary nitrate response genes, including members of the nitrate transporter families NRT1 and NRT2 and the nitrate and nitrite reductase genes NIA1, NIA2, and NiR, are induced. These responses are mediated by signaling pathways that include the nitrate transceptor NRT1.1 (13,14), two kinases (CIPK8 and CIPK23) (13,15), and the transcription factors NLP6/7 (16)(17)(18), LBD37/38/39 (19), and SPL9 (12).…”
mentioning
confidence: 99%